Study of Chlorophyll, Carbohydrate and Protein Content of Trigonella foenum graecum (Fenugreek) Irrigated with Different Sources of Water - P. Sharma; A. Bafna; A.R. Batham (International Journal of Research in Chemistry and Environment (IJRCE), 2017)
Water is the vital resource, necessary for all aspects of human and ecosystem survival and health. Depending on the quality, bore water may be used for human consumption, irrigation purposes and livestock watering. Solid waste from industrial units is being dumped near the factories, which react with percolating rainwater and reaches the ground water. The percolating water picks up a large number of heavy metals and reaches the aquifer system and contaminates the ground water. The usage of the contaminated bore water causes the diseases. Therefore the present work was done to know the impact of water from coalmine, boring and pond added to soil on nutritive biochemical parameters of Trigonella foenumgraecum plant. River water was used as control. Carbohydrate content was insignificantly decreased in Trigonella foenumgraecum seedlings irrigated with boring, pond water and increased in seedlings supplied with coalmine water. There was insignificant change in protein content of Trigonella foenumgraecum seedlings when irrigated with boring and pond water but significant decrease was observed when irrigated with coalmine water. Insignificant change observed in total chlorophyll content of Trigonella foenumgraecum seedlings irrigated with boring, pond and coalmine water. Chlorophyll (a) was significantly decreased in plants irrigated with pond water. Chlorophyll-(b) was insignificantly increased in Trigonella foenumgraecum plant irrigated using boring and decreased in plants irrigated with pond, coalmine water as compared to control. It can be concluded from the present study that boring, pond and coalmine water can be used to irrigate leafy vegetable.